Characterization of Kimchi Flavor with Preconcentration by Head Space Solid-Phase Microextraction and Stir Bar Sorptive Extraction and Analysis by Gas Chromatography-Mass Spectrometry. (24th May 2019) - Hwang, Ye-Seul; Lee, Hae-Won; Chang, Ji Yoon; Seo, Hye Young
Abstract: Kimchi is a traditional fermented vegetable, known for its complex flavor. Herein, we compared compounds related to the kimchi flavor, identified by gas chromatography-mass spectrometry (GC-MS) with the developed solid phase microextraction (SPME) and stir bar sorptive extraction (SBSE) techniques. Although headspace-solid phase microextraction (HS-SPME) detected more volatile compounds than nondestructive-headspace-solid-phase microextraction (ND-HS-SPME), those identified by ND-HS-SPME were considered closely related to the flavor of the intact kimchi. Furthermore, direct immersion-stir bar sorptive extraction (DI-SBSE) detected more volatile and nonvolatile compounds than headspace-stir bar sorptive extraction (HS-SBSE), while more sulfur compounds were identified by HS-SBSE. Therefore, we recommend the use of the HS-SPME method using a divinylbenzene/carboxen/polydimethylsiloxane fiber for identifying compounds related to the kimchi flavor. In addition, principal component analysis showed ND-HS-SPME and HS-SBSE to be closely clustered. Overall, we estimated that the samples obtained via the nondestructive sample preparation emits fewer polar volatile flavor compounds than those obtained using the destructive sample preparation. Considering the findings presented herein, we believe that this study contributes to optimizing the flavor analysis of kimchi and other fermented vegetables.